2011
DOI: 10.1214/11-aoas489
|View full text |Cite
|
Sign up to set email alerts
|

Efficient emulators of computer experiments using compactly supported correlation functions, with an application to cosmology

Abstract: Statistical emulators of computer simulators have proven to be useful in a variety of applications. The widely adopted model for emulator building, using a Gaussian process model with strictly positive correlation function, is computationally intractable when the number of simulator evaluations is large. We propose a new model that uses a combination of low-order regression terms and compactly supported correlation functions to recreate the desired predictive behavior of the emulator at a fraction of the compu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 32 publications
(38 reference statements)
0
110
0
Order By: Relevance
“…An orthogonal approach is to perform approximate GP regression, and a common theme in that literature is sparsity, leading to fast matrix decompositions (e.g., Kaufman et al 2012;Sang and Huang 2012). Again, the expansion of capability is one-to-two orders of magnitude, albeit without tapping supercomputer resources which is more practical for most applications.…”
Section: Supercomputing and Sparse Approximation For Big Datamentioning
confidence: 99%
See 3 more Smart Citations
“…An orthogonal approach is to perform approximate GP regression, and a common theme in that literature is sparsity, leading to fast matrix decompositions (e.g., Kaufman et al 2012;Sang and Huang 2012). Again, the expansion of capability is one-to-two orders of magnitude, albeit without tapping supercomputer resources which is more practical for most applications.…”
Section: Supercomputing and Sparse Approximation For Big Datamentioning
confidence: 99%
“…Again, the expansion of capability is one-to-two orders of magnitude, albeit without tapping supercomputer resources which is more practical for most applications. For example, Kaufman et al (2012) reported on an experiment with N = 20000. Some approaches in a similar vein include fixed rank kriging (Cressie and Johannesson 2008) and using '''pseudo-inputs" (Snelson and Ghahramani 2006).…”
Section: Supercomputing and Sparse Approximation For Big Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This becomes problematic when n goes beyond 10 3 −10 4 , and there is currently a large body of literature proposing alternative computation procedures for larger values of n [17,30,31,55].…”
Section: Current Research Questionsmentioning
confidence: 99%